2020
DOI: 10.1177/0894439320928240
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Data Quality of a National Sample of Young Sexual and Gender Minorities Recruited Using Social Media: The Influence of Different Design Formats

Abstract: Social media recruitment is no longer an uncharted avenue for survey research. The results thus far provide evidence of an engaging means of recruiting hard-to-reach populations. Questions remain, however, regarding whether the data collected using this method of recruitment produce quality data. This article assesses one aspect that may influence the quality of data gathered through nonprobability sampling using social media advertisements for a hard-to-reach sexual and gender minority youth population: recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…More information about the study design, recruitment, implementation, and data management can be found elsewhere. 24 We restricted the sample to sexually experienced transgender youth who self-reported being HIV negative or did not know their status and provided answers to all questions included in our analysis. Our analytic sample contained 1029 participants.…”
Section: Samplementioning
confidence: 99%
“…More information about the study design, recruitment, implementation, and data management can be found elsewhere. 24 We restricted the sample to sexually experienced transgender youth who self-reported being HIV negative or did not know their status and provided answers to all questions included in our analysis. Our analytic sample contained 1029 participants.…”
Section: Samplementioning
confidence: 99%
“…They choose for each social media platform, the techniques used for data capture, analysis and processing with the satisfied data quality model. The purpose of [23] is to address the issues of measurement and representativeness of data using the results of a study in which social media advertisements is used for a hard-to-reach sexual and gender minority youth population. They examine measures of data quality such as exiting the survey before completion, commonly known as "break-off", in addition to using the nonsubstantive responses to questionnaire questions such as "prefer not to answer" and "don't know".…”
Section: Rq2: What Are the Most Important Dimensions And Metrics To A...mentioning
confidence: 99%
“…Section 2 2.3 Online surveys during the COVID-19 pandemic reported poorer mental health status (Choi et al 2017). Stern et al 2020 used Facebook to recruit young men in the United States from sexual minorities. While they found that using a video vs. using an image in the advertisement made no difference in the response rates, they also observed that respondents who entered the survey through the ad with the image had fewer nonsubstantive answers than those who entered the survey through the ad with the video.…”
Section: Topical Self-selection In Facebook Surveysmentioning
confidence: 99%